(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to: To identify the impact of cognitive load theory on the achievement of students in the Department of Technical Education in the subject of curriculum and writing analysis. To achieve the goal of the research، the research formulated the following null hypothesis (There are no statistically significant differences at the level of (0.05) between the average score of the experimental group’s request and the control group’s request in the pre- and post-cognitive achievement test). The research used the experimental method، and the choice of the experimental design adopted in the research was the experimental design with a Tight adjustment level of control for two groups (experimental and control) that took the cognitive achievement test before and after. It was as if the research community consisted of the students of the fourth grade - the Department of art Education - the College of Basic Education - Al-Mustansiriya University - the morning study and for the academic year 2023-2024، and it consisted of 136 students، male and female، distributed into four sections. As for the research sample، the number of students was (68) and his students were chosen in a random way because the population is close to homogeneity. The researcher carried out the process of equivalence in some variables، including (required age، previous experience). The researcher prepared a cognitive achievement test consisting of (20) items، which is one of The test demonstrated objectivity (multiple choice)، and the validity of the test was obtained after presenting it to a group of experts and arbitrators، as well as ensuring that the test was proven using a method. (Repeat the test) The null hypothesis was rejected and the alternative hypothesis was accepted. Based on the role of theory in improving learners’ achievement، I propose that the research conduct a study of the theory of cognitive load and its relationship to the educational motivation for students in preparatory studies